Examinando disparidades na sentença: vieses e categorização grupal por motivações ideológicas e de preconceito - Almeida Segundo, Damião Soares de (2019)
In addition to the legally established criteria guiding the decision in the judicial sphere, judges are influenced by socioral bias and bias arising from human cognitive limitations. In Brazil, the majority of blacks are blacks with low schooling and income, who accumulate disadvantages throughout life. In criminal justice, the disparities in the sentence can be understood from the influence of legal and extralegal variables. Sentencing surveys, or decision-making, have mainly highlighted the role of the class and race of the accused and the victim; as well as of ideological attitudes such as authoritarianism and social dominance of the judge. In this context, the present study sought to (1) organize a theoretical framework to support empirical studies in Psychology of Judgment and (2) to know the differences of verdict in a simulated homicide trial involving poor black and white middle class alternating as defendant or victim; considering the levels of ideological attitudes and prejudices of the judge. To reach the first objective, different areas of knowledge that investigate decision-making have been integrated. Then, a quasi-experimental trial simulation with factorial design 2 (race / class intersection: poor black and white middle class) x 2 (defendant and victim) was carried out. There were 396 subjects, mostly female (59.6%), white (61.4%), aged between 18 and 64 years (M = 26.9, SD = 8.4). Participants responded to an online questionnaire that contained: scale of modern racism, class scale of prejudice, subscale of right-wing authoritarianism, scale of orientation to social dominance and a scenario of homicide trial. Analyzes of descriptive, comparative groups and inferential statistics were performed using SPSS software. In general, the results indicated: a) a condemnatory position on the part of the participants, especially in cases where the victim was black and poor; b) low levels of right-wing authoritarianism, social dominance, modern racism and class prejudice for most of the sample; and c) self-identified participants with the right presented a more protective response pattern in relation to the accused and the white middle-class victim, while those on the left were more protective of the black and poor victim. Limitations and future directions were indicated. The overall goal is considered to have been achieved as the study has contributed to the growing body of literature examining the ways in which socioral bias can interfere in the judges' decision-making.